Effects of Trace Metal Concentrations on the Growth of the Coral Endosymbiont Symbiodinium kawagutii - Rodriguez, Irene B.; Lin, Senjie; Ho, Jiaxuan; Ho, Tung-Yuan (Frontiers in Microbiology, 2016)
Symbiodinium is an indispensable endosymbiont in corals and the most important primary producer in coral reef ecosystems. During the past decades, coral bleaching attributed to the disruption of the symbiosis has frequently occurred resulting in reduction of coral reef coverage globally. Growth and proliferation of corals require some specific trace metals that are essential components of pertinent biochemical processes, such as in photosynthetic systems and electron transport chains. In addition, trace metals are vital in the survival of corals against oxidative stress because these metals serve as enzymatic cofactors in antioxidative defense mechanisms. The basic knowledge about trace metal requirement of Symbiodinium is lacking. Here we show that the requirement of S. kawagutii for antioxidant-associated trace metals exhibits the following order: Fe >> Cu/Zn/Mn >> Ni. In growth media with Cu, Zn, Mn and varying Fe concentrations, we observed that Cu, Zn and Mn cellular quotas were inversely related to Fe concentrations. In the absence of Cu, Zn and Mn, growth rates increased with increasing inorganic Fe concentrations up to 1250 pM, indicating the relatively high Fe requirement for Symbiodinium growth and potential functional complementarity of these metals. These results demonstrate the relative importance of trace metals to sustain Symbiodinium growth and a potential metal interreplacement strategy in Symbiodinium to ensure survival of coral reefs in an oligotrophic and stressful environment.